Anatol Rosenfeld: o crítico como pensador - Cardoso, Maria Abadia (2014)
Favoring the intrinsic relationship between History and Aesthetics, specifically an approach that seeks to understand the historicity within the critical theory and creative practice, this research was based on investigate the intellectual production of Anatol Rosenfeld. This production mainly includes texts of literary theory and critics, as well as theory and theatrical práxis. Thus, literature and mostly theater were fundamental languages to investigate the materiality that the aesthetic and the historical dimensions, as well as its interfaces, acquire in Anatol Rosenfeld s writings. In order to understand the uniqueness of its construction, it was necessary to "map" not only their theoretic, but specially their historic referential. Among others, important biases for the development of this work were: intellectual activities and political perspectives, past and present, art and politics, theory and critic. His writings, considered here as documents, were crucial to situate the historicity of his constructions.